Utilization of Residual Carrageenan Extract from Eucheuma Cottonii Seaweed Into Bioethanol - Nia Yuliani; RTM Sutamiharja; Aditya Prihantara (Indonesian Journal of Applied Research (IJAR), 2020)
In the process of processing seaweed will produce residual waste from carrageenan extraction, and the residue still contain cellulose, lignin, hemicellulose, pectin, and other organic materials that can be processed into bioethanol. This research aimed to utilize the residual carrageenan extracted from seaweed Eucheuma cottonii into bioethanol. The research method includes acid hydrolysis process using 3% sulfuric acid at a temperature of 70-80oC for 30 minutes, followed by a fermentation process using yeast Saccharomyces cerevisiae with a ratio of 1: 0.006 for hydrolyzate and yeast, fermentation time treatment 1, 3, 6, 9 and 12 days at temperature 25o-30oC. Fermentate at 78oC, measured in degrees of acidity (pH), volume, and levels of bioethanol. The results showed that the residual carrageenan extract containing carbohydrates as un-extracted carrageenan was 5.01%, hemicellulose was 7.12%, cellulose was 0.96%, and lignin was 8.26%. The level of bioethanol produced from the residual carrageenan extraction was 2.57% and, the yield was 32.64% with a fermentation time of 6 days as the optimal time.